Serious Sport Injury, Motivation and Burnout: Can Self-Determined Motivation Predict Burnout in Elite Handball Players? - Rasoul Arabi; Mohammad Keshtidar; Mohammadesmaiel Afzalpour; Jafar Khoshbakhti; Mohammad Rahimi (University of Tehran, 2010)
In the past 10 years, the amount of research conducted on psychological aspects of sport injury has been increasing. The purpose of this study was to predict the burnout according to the self-determined motivation in Iranian elite handball players before and after the injury. The subjects were 28 injured elite handball players who did not participate in competitions for 4 weeks due to their injuries. Participants completed Sport Motivation Scale (Pelletier et al., 1999) and an athletic burnout questionnaire (Raedeke & Smith, 2001) at the beginning of the competitive season. Paired-sample t test, Pearson correlation coefficient and Multiple regression test were used to analyze the data (P